Experimental and Numerical Analysis of the Aerodynamics of Peregrine Falcons during Stoop Flight - C. Lagemann; E.R. Gowree; C. Jagadeesh; E. Talboys; C. Brücker (Deutsche Gesellschaft für Luft- und Raumfahrt - Lilienthal-Oberth e.V., 2018)
Amongst birds, peregrine falcons (Falco peregrinus) are well-known for their unique high-speeds during stoop. A combination of time-resolved stereoscopic particle-image velocimetry (TR-SPIV), surface oil flow visualization (SOFV) and large-eddy simulations (LES) is used to analyze the complex flow over life-size models of peregrine falcons. lt is demonstrated that the exceptional manoeuvrability of peregrine falcons during stoop is attributed to vortex dominated flow promoted by their morphology and their wing shapes. Both, experiments and simulations, revealed the presence of vortices emanating from the neck and the dorsal region due to a strong spanwise flow enhancing mixing for a quick reattachment to ensure a fully attached flow over the tail feather. The stronger wing and tail vortices further provide vortex induced lift for pitch and roll control.